Ownership Structure and Sustainability Reporting Disclosures of Listed Multinational Companies in Nigeria - Adejumo, Isiaka Adebisi; Ololade, Babatunde Moses; Sanni, Michael Rotimi; Adeyanju, David Lanre (International Journal of Economics and Financial Issues, 2025)
The disclosure of quality sustainability reporting information has become a global necessity because of the need to meet corporate stakeholders’ financial and non-financial information needs for economic decision-making. The extant scholarly evidence has neglected the contributing role of ownership structure in the disclosure of sustainability information among multinational listed firms in Nigeria. Hence, this present study explores the effect of ownership structure on sustainability reporting disclosure of ten (10) purposively selected listed multinational firms in Nigeria spanning 2018-2022. The empirical analysis was undertaken using fully modified ordinary least square (FMOLS) and dynamic ordinary least square (DOLS) to analyze the secondary panel data obtained from annual reports of the listed firms. Findings revealed that managerial ownership, institutional ownership, foreign ownership and family ownership have positive significant effect on sustainability reporting disclosure, while government ownership showed a negative significant relationship with sustainability reporting disclosure. Also, findings revealed that the combined effect of all the variables are positively related with the sustainability reporting disclosure. The study recommended that government ownership of multinational companies should be discouraged by corporate stakeholders.